Three-dimensional printed bioresorbable scaffold for maxillofacial bone reconstruction: A Scoping Review - Malzoni, Carolina Mendonça de Almeida [UNESP]; Oliveira, Jovânia Alves; Soares, Lélio Fernando Fereira [UNESP]; Chimirri, Marcella Cunha; Almeida, Daniel Augusto de Faria; Pigossi, Suzane Cristina; Marcantonio Junior, Elcio [UNESP] (FapUNIFESP (SciELO), 2024)
This scoping review aimed to provide an overview of current advancements in virtual planning and custom-made 3D-printed bioresorbable scaffolds, and to evaluate their clinical outcomes in maxillofacial reconstructive surgeries. Electronic searches of PubMed, EMBASE, Web of Science, Scopus, and Cochrane Library databases were conducted for publications up to June 2024. Included in the review were reports evaluating patients who underwent maxillofacial bone defect reconstruction using virtual planning and custom-made 3D-printed bioresorbable scaffolds. Data on postoperative complications, new bone formation, scaffold resorption, dental implant success/survival, and patient satisfaction were collected. The electronic search found 5799 results (3438 unique citations). A total of 54 studies were evaluated for full-text reading, of which 41 were excluded based on the inclusion criteria. Thirteen studies (6 case reports, 5 case series, one prospective clinical study and one randomized clinical trial) were included. These studies assessed the effectiveness of 3D-printed scaffolds in reconstructing maxillofacial defects, bone augmentation for dental implant placement, and regeneration of periosseous defects. Most of the 3D-printed scaffolds were biocompatible and did not cause local or systemic adverse events. However, some postoperative complications were reported, including graft exposure, wound dehiscence, and local infection. Overall, the 3D-printed scaffolds demonstrated favorable dimensional compatibility with deformities, provided durable support, promoted bone formation, achieved adequate bone union with host bone tissues, and supported dental implant placement without additional guided bone regeneration. In conclusion, custom-made 3D-printed bioresorbable scaffolds, guided by virtual planning, present a promising option for maxillofacial reconstruction due to their accuracy, osteoconductivity, and biocompatible properties.
Keywords: Biocompatible materials; Bone graft; Bone regeneration; Three-Dimensional Printing